Regional High Iron in the Substantia Nigra Differentiates Parkinson’s Disease Patients From Healthy Controls - Ghassaban, Kiarash; He, Naying; Sethi, Sean Kumar; Huang, Pei; Chen, Shengdi; Yan, Fuhua; Haacke, Ewart Mark (Frontiers in Aging Neuroscience, 2019)
Background: Iron is important in the pathophysiology of Parkinson’s disease (PD) specifically related to degeneration of the substantia nigra (SN). Magnetic resonance imaging can be used to measure brain iron in the entire structure but this approach is insensitive to regional changes in iron content. Objectives: The goal of this work was to use quantitative susceptibility mapping (QSM) and R2* to quantify both global and regional brain iron in PD patients and healthy controls (HC) to ascertain if regional changes correlate with clinical conditions and can be used to discriminate patients from controls. Methods: Susceptibility and R2* maps of 25 PD and 24 HC subjects were reconstructed from data collected on a 3T GE scanner. For the susceptibility maps, three-dimensional regions-of-interest (ROIs) were traced on 8 deep gray matter structures and an age-based threshold was applied to define regions of high iron content. The same multi-slice ROIs were duplicated on the R2* maps as well. Mean susceptibility values of both global and regional high iron content along with global R2* values were measured and compared not only between the two cohorts, but also to susceptibility and R2* baselines as a function of age. Finally, clinical features were compared for those PD patients lying above and below the upper 95% regional susceptibility-age prediction intervals. Results: The SN was the only structure showing significantly higher susceptibility in PD patients compared to controls globally (p < 0.01) and regionally (p < 0.001). The R2* values were also higher only in the SN of PD patients compared to the healthy cohort (p < 0.05). Furthermore, those patients with abnormal susceptibility values lying above the upper 95% prediction intervals had significantly higher united Parkinson’s diagnostic rating scores. R2* values had larger errors and showed larger dispersion as a function of age than QSM data for global analysis while the dispersion was significantly less for QSM using the regional high iron content. Conclusions: Abnormal iron deposition in the SN, especially in regional high iron areas, could serve as a biomarker to distinguish PD patients from HC and to assess disease severity.